The effect of ZrCl4, Al(NO3)3 and Na2SiO3 precursors concentration on particle size as dental composites filler through spray pyrolysis method - Karlina, Elin; Idznihaq, Khairina; Febrida, Renny; Andiesta, Niekla Survia (Padjadjaran Journal of Dentistry, 2023)
ABSTRACTIntroduction: one of the important components in dental composites is a filler which can be made through various methods, including spray pyrolysis. In the spray pyrolysis method, some factors determine the size and morphology of the resulting filler particles, one of which is the concentration of precursors. This study aimed to analyze the effect of precursor concentration on the particle size produced using the spray pyrolysis method. Methods: in this experimental laboratory study, zirconia-alumina-silica particles were synthesized using the spray pyrolysis method. The precursor solution consisted of ZrCl4, Al (NO3)3, and Na2SiO3 with a concentration variation of (0.1; 0.2; and 0.3) M. The furnace temperature was set at 750°C, and the electric precipitator temperature was 100°C with a feed rate of 3L/min. Then, the tests performed were using PSA (Particle Size Analyzer), and XRF (X-Ray Fluorescence). Results: The results showed that the best zirconia alumina silica filler particle with the smallest size is the result with a concentration of 0.1 M and its size was 618.6 nm. The particle size for 0.2 M was 911.9 nm and 1799.4 nm for 0.3 M.  According to XRF test results the zirconia alumina silica filler system contains all the precursor elements. Conclusions: The effect of precursor concentration on the particle size produced using the spray pyrolysis method showed that the smaller the precursor concentration used, the smaller the particle size produced. The best results from synthesizing a filler system with a concentration of 0.1 M precursor solution. All the results are in submicron and micron size, and could be used as the component of dental composites.Keywords: precursors concentration, particle size, spray pyrolysis, dental composites filler